Roles and work–family conflict: how role salience and gender come into play. Issue 8 (28th April 2021) - Erdogan, Irmak; Ozcelik, Hakan; Bagger, Jessica
Abstract: In this study, we explored how the salience of work and family roles relate to work–family conflict and whether and how these relationships differ for men and women. Conducting latent class cluster analysis in a sample of 251 working professionals across three organizations, we identified four profiles of employees who differed on relative salience of work and family roles. Respondents who organized their roles in a salience hierarchy and assigned greater salience to either the work or family role (i.e., those in a profile of predominant work salience or predominant family salience) were found to experience less work–family conflict as compared to those assigning high levels of salience to both roles (i.e., profile of dual high-salience) or those assigning low levels of salience to both roles (i.e., profile of dual low-salience). Results suggest that clarifying priorities between work and family roles may result in less work–family conflict. Moreover, findings show that contrary to the traditional view of gender and work–family conflict, organizing work and family roles in a salience hierarchy with a predominant non-traditional gender role is associated with less work–family conflict, especially for women. Implications of these findings for research and practice were discussed.